Characterizing Pediatric ECMO Outcomes and Access: A State-Wide Analysis in New South Wales, Australia - Moynihan, Katie M.; Schneuer, Francisco J.; Festa, Marino; Basu, Shreerupa; Singhal, Nitesh; Liava'a, Matthew; Ravindranathan, Hari; Nassar, Natasha (Journal of Pediatric Intensive Care, 2024)
This study examines impacts of social determinants of health (SDoH) on pediatric extracorporeal membrane oxygenation (ECMO) (1) outcomes and (2) utilization. This is a state-wide retrospective study of children (≤15 years) in New South Wales (NSW), Australia (2002–2020). ECMO-supported patients were identified from NSW Admitted Patient Data Collection, with diagnoses defined using International Classification of Diseases version 10-Australian Modification codes. SDoH included socio-economic indexes for area index of social disadvantage (quintiles), residence (metropolitan-Sydney vs. regional/remote), and insurance. Survival analyses assessed associations with SDoH and clinical characteristics, with multivariable analyses restricted to cardiac patients. For utilization analyses, children with equivalent diagnoses and no comorbid contraindications who died without ECMO comprised the comparative cohort. Of 267 ECMO runs, (238 in 229 NSW residents) its use increased over time. Cardiac indications predominated (84%) with 43% in neonates and 19% in unplanned admissions. Overall, 96% were Australian-born and 76% from metropolitan-Sydney. For outcomes, 36% of deaths occurred in-hospital, with 58% of patients alive at study conclusion (median follow-up: 1.3 [interquartile range: 0–6.2] years). Higher mortality was observed in the neonatal age group, and diaphragmatic hernia diagnoses, while respiratory failure was associated with lower mortality (log-rank p < 0.05). There was no association between mortality in children supported on ECMO and SDoH (p > 0.05). Considering utilization, patients who died without ECMO were more likely to live in regional/remote/under-resourced areas and have public insurance versus ECMO-supported children. Population-standardized ECMO rates were similar by SDoH. We identified disparate ECMO utilization but equivalent outcomes according to SDoH. Data support ongoing commitment to developing approaches that promote equitable access to life-saving therapies across demographic and geographic barriers.
Keywords: children; retrospective study; extracorporeal membrane oxygenation; New South Wales; social determinants of health; Australia; survival analysis